2016
DOI: 10.3390/met6110276
|View full text |Cite
|
Sign up to set email alerts
|

Nano-ZnO Particles’ Effect in Improving the Mechanical Response of Mg-3Al-0.4Ce Alloy

Abstract: Magnesium based nanocomposites, due to their excellent dimensional stability and mechanical integrity, have a lot of potential to replace the existing commercial Al alloys and steels used in aerospace and automotive applications. Mg-Al alloys are commercially used in the form of AZ (magnesium-aluminum-zinc) and AM (magnesium-aluminum-manganese) series in automobile components. However, the Mg 17 Al 12 phase in Mg-Al alloys is a low melting phase which results in a poor creep and high temperature performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
1
11
1
Order By: Relevance
“…From the microstructural analysis of secondary phases, nanoparticles, and grain sizes, the results confirm that the nanoparticles contributed to the further grain refining of the material. This is in contrary to the previously reported alloy nanocomposites, where marginal grain coarsening was observed when nanoparticles were added to magnesium-based alloys [14,21]. In previous works, it was reported that the nanoparticles, in certain magnesium matrices, alter the mechanism of dynamic recrystallization, from Zener pinning to localized particle stimulated nucleation, causing an inhomogeneity and; therefore, a bimodal grain size across the nanocomposite [14].…”
Section: Structural Characterizationcontrasting
confidence: 76%
“…From the microstructural analysis of secondary phases, nanoparticles, and grain sizes, the results confirm that the nanoparticles contributed to the further grain refining of the material. This is in contrary to the previously reported alloy nanocomposites, where marginal grain coarsening was observed when nanoparticles were added to magnesium-based alloys [14,21]. In previous works, it was reported that the nanoparticles, in certain magnesium matrices, alter the mechanism of dynamic recrystallization, from Zener pinning to localized particle stimulated nucleation, causing an inhomogeneity and; therefore, a bimodal grain size across the nanocomposite [14].…”
Section: Structural Characterizationcontrasting
confidence: 76%
“…However, when nanocomposites were compared to alloys in terms of the grain sizes (keeping the processing parameters the same), it is seen that the nanocomposites did not achieve as effective grain refinement as alloys, i.e., grain refinement was not possible to less than 5 lm in case of most Mg nanocomposites [11]. Such results are intriguing as the alloy nanocomposites reported previously also exhibited a similar grain coarsening compared to the alloys [15]. The reason behind this has not been discussed so far, particularly for Mg- based nanocomposites, to the authors' best knowledge.…”
Section: Resultsmentioning
confidence: 72%
“…An upsurge in the processing and fabrication of lightweight magnesium (Mg) and the associated alloys/nanocomposites, typically for weight-sensitive applications such as in the aerospace industry, has been observed in the recent past [1][2][3]. A number of components in the aircraft interiors, such as passenger seats, overhead compartments, folding tables and food trolleys, and transmission casings, have the potential to use magnesium [4].…”
Section: Introductionmentioning
confidence: 99%